Stray Dogs as a Public Health Threat: A Comprehensive Review of Hydatid Cyst (Cystic Echinococcosis) Transmission and Control - Rabia Ali Aboud (Jurnal MIPA dan Pembelajarannya, 2026)
Hydatid cyst disease, or cystic echinococcosis, is a significant zoonotic parasitic infection caused by the larval stage of Echinococcus granulosus. Dogs act as definitive hosts and play a central role in maintaining the transmission cycle, particularly in areas with large stray dog populations. Stray dogs contribute substantially to environmental contamination through the shedding of parasite eggs, increasing the risk of human infection.Humans become accidental intermediate hosts through ingestion of contaminated food, water, or direct contact with infected dogs. The disease is widely distributed in developing countries and imposes considerable health and economic burdens, especially in regions with poor slaughterhouse hygiene and limited veterinary control.This review summarizes current knowledge on the epidemiology, life cycle, transmission pathways, and risk factors of hydatid cyst infection associated with stray dogs. It also highlights clinical manifestations, diagnostic methods, and prevention strategies.Effective control requires integrated measures, including dog population management, regular deworming, improved veterinary surveillance, and public health education. The implementation of a One Health approach is essential for reducing transmission and minimizing the impact of hydatid disease on public health.